Afghan Women After Talibanization - S. Sumitra; Mohammad Ramin Hakimy; Basel Abou Rokba (Jurnal Multidisiplin Madani, 2023)
Bread, Work, and Freedom nowadays Afghan women slogans in streets of the Kabul capital of Afghanistan who is suffering from fundamentalism prison of Taliban. It is the voice of those who cry out for the depth of their helplessness, suffering, and loneliness under the rule of the Taliban. While screaming these slogans they have to tolerate the insult, humiliation, and mayhem of Taliban forces. With the rise of the Taliban, the demands, rights, and freedoms of Afghan women were limited to the Taliban's Shari'a and their interpretation of Islam. After nearly four months of Taliban rule, have brought nothing but poverty, hunger, unemployment, deprivation, and suffering to women. Moreover, in the darkest day and most symbolic activity after the Taliban took control of Kabul, the Ministry of Women's Affairs' door was closed by the Taliban, and the ministry was renamed "Enjoining the Good and Forbidding the Evil or (امر به معروف و نهی از منکر)." All-female employees of the ministry were told that they no longer had the right to return to work. The suffering of Afghan women in Afghanistan's traditional and highly anti-feminist structure goes beyond that. They were captive to Afghanistan's tradition, religion, patriarchal and anti-feminist society for many years and lived in poverty and deprivation. Over the past two decades, women in various political and social arenas have sought to make their mark. They tried to change the traditional, patriarchal laws, structures, and patterns in their favor. But with the rise of the Taliban, many of their aspirations were dashed. The current study uses a descriptive-analytical approach to answer the following questions: what is the situation of women after the Taliban took control over Afghanistan? what is the rule of women in Afghan society? How do the Taliban violate women’s rights? What are women’s rights according to Islamic sharia and international human rights law?